Potential vorticity structure of embedded convection in a warm conveyor belt and its relevance for large-scale dynamics - A. Oertel; M. Boettcher; H. Joos; M. Sprenger; H. Wernli (Weather and Climate Dynamics, 2020)
Warm conveyor belts (WCBs) are important airstreams in extratropical cyclones. They can influence large-scale flow evolution by modifying the potential vorticity (PV) distribution during their cross-isentropic ascent. Although WCBs are typically described as slantwise-ascending and stratiform-cloud-producing airstreams, recent studies identified convective activity embedded within the large-scale WCB cloud band. However, the impacts of this WCB-embedded convection have not been investigated in detail. In this study, we systematically analyze the influence of embedded convection in an eastern North Atlantic WCB on the cloud and precipitation structure, on the PV distribution, and on larger-scale flow. For this reason, we apply online trajectories in a high-resolution convection-permitting simulation and perform a composite analysis to compare quasi-vertically ascending convective WCB trajectories with typical slantwise-ascending WCB trajectories. We find that the convective WCB ascent leads to substantially stronger surface precipitation and the formation of graupel in the middle to upper troposphere, which is absent for the slantwise WCB category, indicating the key role of WCB-embedded convection for precipitation extremes. Compared to the slantwise WCB trajectories, the initial equivalent potential temperature of the convective WCB trajectories is higher, and the convective WCB trajectories originate from a region of larger potential instability, which gives rise to more intense cloud diabatic heating and stronger cross-isentropic ascent. Moreover, the signature of embedded convection is distinctly imprinted in the PV structure. The diabatically generated low-level positive PV anomalies, associated with a cyclonic circulation anomaly, are substantially stronger for the convective WCB trajectories. The slantwise WCB trajectories lead to the formation of a widespread region of low-PV air (that still have weakly positive PV values) in the upper troposphere, in agreement with previous studies. In contrast, the ...